2020
DOI: 10.1007/s40737-020-00203-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 on Mental Health Rehabilitation Centers

Abstract: The SARS-CoV-2 outbreak is an unprecedented event in modern history worldwide. To facilitate speedy and smooth recovery during this time period, an added responsibility is placed upon rehabilitation center counselors, staff and management. In this paper we expose the role that psychiatric rehabilitation plays during the COVID-19 crisis. Since

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 17 publications
0
14
0
2
Order By: Relevance
“…Resilience and social support are essential sources to facilitate mental well-being and improve people's understandings of meaning in life ( 17 , 26 ). Recent studies reported that people might not seek help to relieve themselves due to the low resilience and perceived social support under the stress of the COVID-19 pandemic, which in turn results in new mental health problems ( 3 , 4 ). In the case of the current study, COVID-19 related stress exacerbated the prevalence of depressive and anxiety symptoms by decreasing the Chinese people's perceived social support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resilience and social support are essential sources to facilitate mental well-being and improve people's understandings of meaning in life ( 17 , 26 ). Recent studies reported that people might not seek help to relieve themselves due to the low resilience and perceived social support under the stress of the COVID-19 pandemic, which in turn results in new mental health problems ( 3 , 4 ). In the case of the current study, COVID-19 related stress exacerbated the prevalence of depressive and anxiety symptoms by decreasing the Chinese people's perceived social support.…”
Section: Discussionmentioning
confidence: 99%
“…Another Chinese study found that 53.8% of the respondents had experienced psychological impacts of the COVID-19 pandemic on a moderate or severe level, with 8.1% of respondents reporting moderate to severe stress levels by early 2020 (2). These negative mental health outcomes may attribute to the stress induced by the COVID-19 pandemic, as some researchers indicated that COVID-19 related stress made people more vulnerable to developing mental health issues (3,4). Recent studies further confirmed an association between COVID-19 related stress and negative mental health outcomes (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, this evidence suggests a greater vulnerability to COVID-19 sequelae for people already suffering from cognitive impairment (e.g., dementia, Parkinson's) who need a support network, such as caregivers and social and health services (Aamir et al, 2021). The changes in routine living conditions, such as the lockdown-related difficulties to access the Abbreviations: BAI, beck anxiety inventory; BDI, beck depression inventory; COVID-19, coronavirus disease 2019; GAD-7, generalized anxiety disorder 7; HADS, hospital anxiety and depression scale; MCS, mental component summary; MoCA, montreal cognitive assessment; NMSS, non-motor symptoms scale; NPI-Q, neuropsychiatric inventory questionnaire; PCS, physical component summary; PDQ-8, parkinson's disease questionnaire-8; PHQ-9, personal health questionnaire 9; PSS, perceived stress scale; QoL, quality of life; QoL-AD, quality of life in alzheimer's disease; QUIP-RS, questionnaire for impulsive-compulsive disorders in parkinson's disease-rating scale; RMBPC, revised memory and behavior problem checklist; SARS-CoV-2, severe acute respiratory syndrome coronavirus 2; SAS, zung's self-rating anxiety scale; SDS, zung's self-rating depression scale; SF-8, short form health survey; SWEMWBS, short warwickedinburgh mental well-being scale; ZBI, zarit burden interview.…”
Section: Introductionmentioning
confidence: 88%
“…In most mental health services, outpatient contacts tended to decline during the pandemic though, in some services, they were preserved and, in the catchment area of the inpatient unit under study, increased, as a consequence of different choices in the application of restriction criteria and in service activity[ 12 - 14 ]. These findings suggest that the distinctive organization of mental health services in Lombardia Region, each established according to a community-based model of care with a multidisciplinary team serving a well-defined catchment area under the coordination of the local department of mental health, had the potential: (1) To face and overcome the limitations imposed by the pandemic by changing allocation of human resources and remodeling interventions in order to meet patients’ new and different needs; and (2) To implement a shared recommendation that all patients, and especially so those with severe mental disorder, were not left alone and forgotten during the COVID-19 crisis and received regular assessment, emotional support and treatment ( e.g., long-acting antipsychotics) by telephone consultations, face-to-face interviews or, in selected cases, domiciliary visits[ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%